The level of obesity awareness among students at higher learning institutions / Naimah Shakirah Mohamed and Norhidayu Rahim - Mohamed, Naimah Shakirah; Rahim, Norhidayu (Faculty of Administrative Science and Policy Studies, 2012)
University Teknologi Mara (UiTM) and Universiti Teknikal Malaysia (UTeM) are two higher learning institutions that located in Melaka Tengah District, Melaka that offer degree study. Both of the institutions are nearer to each other which they having a quite similar of the location on food consumption. Those students will take their breakfast or lunch or dinner or all of the meals at this area as near to their institution. One of the trends of both of the students of institution that can be observed is food consumption offer along the Jalan Hang Tuah. This area was surrounded with friendly environment that provide students with variety of food to be consume. However, the main purpose of the research paper is to evaluate the level of awareness of the obesity among them as a student. And, indirectly increase their awareness toward this matter concern. The issue of obesity has alarming the health level of Malaysians as ranked is ranked sixth in the Asia-Pacific region and has the highest obesity rates in Southeast Asia (Malaysiatoday,2011). In order to answer this study attempts, 200 of questionnaire distributed to the students of each institutions and received all valid respond.